ANALISIS PERSEPSI WAJIB PAJAK PEMILIK UMKM TERHADAP PENETAPAN KEBIJAKAN PAJAK PENGHASILAN FINAL SESUAI PERATURAN PEMERINTAH NO. 46 TAHUN 2013 (STUDI PADA KPP PRATAMA MALANG UTARA) - Nurpratiwi, Anisa (Jurnal Mahasiswa Perpajakan, 2014)
Accordingly the presence of Government Regulation 46 Year 2013 about Income Tax on Income for Business Or Received Retrieved Taxpayers Who Owns a Certain Gross Circulation an individual taxpayer or a business owner entity with gross turnover till IDR 4, 8 billion for a year can perform their tax obligations with term 1% as a tariff and the gross turnover as a Tax Base, this study aims to describe the perceptions of SME owners taxpayers about final income tax policy of Government Regulation 46 Year 2013 or better known as SME tax in terms of Adam Smith’s tax principles. The method for this study is descriptive research with quantitative approach using a questionnaire survey to taxpayers that registered owners of SMEs in the Tax Office of North Malang. The results: Taxpayer’s perception about the regulation in terms of convenience principle stated in the interval of 3.75 means agrees category Government Regulation 46 Year 2013 comply this principle. In terms of efficiency principle stated in the interval of 3.98 means agrees category. In terms of certainty principle stated in intervals of 2.44 means disagree category. In terms of equality principle stated in the interval of 2.28 means disagree category. Keywords:       Perception, Income Tax, Final Tax, Small and Medium Enterprises (SME), Adam Smith's Tax Principles